Research on intrusion response strategy based on static Bayesian game in mobile edge computing network - Wei FAN; Cheng PENG; Dali ZHU; Yuqing WANG (Tongxin xuebao)
In the mobile edge computing (MEC) environment, the resources of edge nodes are limited.It is difficult to detect the intrusion process accurately, and there is no effective intrusion response strategy to deal with external intrusions.An intrusion detection network structure suitable for mobile edge computing environment was proposed and an intrusion response decision model based on static Bayesian game was established to simulate the network interaction behavior between edge nodes and external intruders.The probability of attackers and defenders in the game process was predicted respectively.The influence of the system resource, the cost of intrusion response, the detection rate and false alarm rate were considered comprehensively by the intrusion response decision model.The response decision of the intrusion detection system was optimized on the basis of the considering both resource consumption of the intrusion detection and the privacy protection of the edge nodes.The factors that affected the decision-making of intrusion response were analyzed, and the experimental basis for the specific application was provided.